Influences of compensation and work environment on employee performance - Wiri Wirastuti; Pricylia Chintya Dewi Buntuang; Risnawati Risnawati (Institute of Computer Science (IOCS), 2024)
This study examines the role of compensation and work environment in influencing employee performance at the Central Sulawesi Province Social Service. This study used a quantitative approach. The population was all employees at the Central Sulawesi Provincial Social Service with 35 people. The determination of the sample used a census technique, which means that the entire population is used as the sample. Data were collected by observing, distributing questionnaires, and tracking secondary data. Data analysis used a multiple regression technique to see the influence of the independent variable on the dependent variable. The results of this study showed that compensation and the work environment simultaneously influence employee performance at the Central Sulawesi Provincial Social Service. Meanwhile, compensation partially does not influence employee performance. On the other hand, the work environment influences employee performance at the Central Sulawesi Provincial Social Service